A Spectrum of Selves Reinforced in Multilevel Coherence: A Contextual Behavioural Response to the Challenges of Psychedelic-Assisted Therapy Development - Whitfield, Henry J. (Frontiers in Psychiatry, 2021)
Psychedelic-assisted therapy research for depression and PTSD has been fast tracked in the United States with the Food and Drugs Administration( FDA) granting breakthrough designations for MDMA (post-traumatic stress disorder) and psilocybin (major depressions) disorder. The psychotherapeutic treatments accompanying these psychedelics has not been well studied and remain controversial . This article reviews the challenges unique to psychedelic-assisted therapy and introduces a newly optimised psychological flexibility model that adapts Contextual Behavioural Science (CBS)/Acceptance and Commitment Therapy (ACT) to those multiple challenges, including ego inflation, traumatic memories, and the perceived presence of entities. A methodology aligned with biological mechanisms, psychological processes and therapeutic contexts may be advantageous for improving outcomes. This model expands ACT by integrating practices and data from psychedelic-assisted therapy research into a Contextual Behavioural Science framework, allowing both fields to inform each other. Psychological flexibility processes are questioned and adapted to a psychedelic context, and interventions that operationalise these processes are considered. The principle through-line of the paper is to consider varied constructs of Self, as understood by these fields, and integrates respective elements of varied self-models, interventions and data into a Spectrum of Selves model for psychedelic-assisted therapy. Secondly the paper examines how to select and retain new self-perspectives and their corresponding behaviours systemically, drawing from evolutionary science principles. A brief yet detailed case example of such behavioural reinforcement is provided, as well as a psychedelic integration checklist to guide the practical implementation of such an approach. This method can enable a coherent therapeutic framework with clear operational relationships between 1) problematic behaviour patterns that an individual wishes to address 2) the guided psychedelic experiences of that individual, and 3) the barriers to maintaining any changes, thus increasing theoretical-practical coherence, broadening treatment benefits and reducing relapse in psychedelic-assisted therapy. Research questions for further developing a CBS-consistent psychedelic-assisted therapy are offered.